Análisis de discurso del vicepresidente Jorge Glas Espinel en el enlace ciudadano N. 470. - Erazo Espinoza, Bryan Jair (2017)
The Government of Rafael Correa starts in 2007 and with this a new form of Government begins in the country, however the new idea called "revolution citizen" changes over the years becoming an authoritarian ideology for opponents, is born the image of a President close to the people of the great popularity, besides emerge leaders of left on the orders of the President, the "new" revolution citizen strengthens its image and introduced a line of power both representative and discursive. The link with the Ecuadorian people called "Links citizens" becomes the most effective weapon of the ruling party, however greater government strategy is set in the style, so there are gesticuladoras such imitations as speech by the Vice President to go to his followers, is a discursive comparison between the two leaders. More beyond of a simple accountability of accounts, is provides as a strategy of speech that intercedes in the opinion public, taking as example to Jorge Glas, who is presented as a possible candidate to future